Immersive technology towards a kineikonic dialogism in challenging the myth of the frame - Lloren, Gregg S. (Plaridel, 2019)
Access online through this link: https://www.plarideljournal.org/article/immersive-technology-towards-a-kineikonic-dialogism-in-challenging-the-myth-of-the-frame